Hybrid tourism and territorial development: The case of voluntourism and alternative tourism in Saudi Arabia - Fridhi, Bechir (Journal of Tourism Management Research, 2025)
This study investigates the role of hybrid tourism, which combines voluntourism and alternative tourism, in fostering territorial development in Saudi Arabia within the framework of Vision 2030. By integrating social participation and sustainable tourism principles, hybrid tourism is examined as a multidimensional tool for economic diversification and community empowerment. Using panel data from Saudi provinces and municipalities spanning 2014 to 2025, the analysis evaluates the impact of hybrid tourism intensity (HTI) on key development indicators, including local tourism employment, entrepreneurship, and social economy dynamics. A robust econometric strategy is employed, incorporating Fixed Effects (FE) to account for unobserved heterogeneity, a Difference-in-Differences (DiD) approach to capture the effects of tourism policy reforms, and Instrumental Variables (IV) estimation to mitigate endogeneity concerns. Additional robustness checks, such as alternative HTI specifications, placebo tests, and clustered standard errors, reinforce the reliability of the findings. Results demonstrate that regions exhibiting higher HTI achieve notable improvements in employment (18–24%), entrepreneurship (15–20%), and social economy development (around 22%), particularly in areas characterized by strong infrastructure, education, and institutional support. The study contributes to existing literature by conceptualizing hybrid tourism as a strategic lever for inclusive and sustainable territorial development in the Gulf region. It also provides actionable insights for policymakers aiming to balance economic growth with social inclusion and environmental sustainability.